Diagnosing Complex Flow Characteristics of Mishrif Formation in Stimulated Well Using Production Logging Tool - Alameedy, Usama; Almomen, Ahmed (Iraqi Journal of Science, 2023)
Production logging is used to diagnose well production problems by evaluating the flow profile, entries of unwanted fluids and downhole flow regimes. Evaluating wells production performance can be easily induce from production logs through interpretation of production log data to provide velocity profile and contribution of each zone on total production. Production logging results supply information for reservoir modeling, provide data to optimize the productivity of existing wells and plan drilling and completion strategies for future wells. Production logging was carried out in a production oil well from Mishrif formation of West Qurna field, with the objective to determine the flow profile and fluid contributions from the perforations after the stimulation job. The measurements were made under shut-in and three choke sizes (60/64”, 46/64” and 32/64”) flowing conditions. Overall, the data quality is acceptable to generate a good analysis. From the flowing surveys, it was observed that just the intervals 2250-2285 m and 2335-2375 m are contributing to the total well production while the well was flowing through the chokes 60/64” and 46/64”. However, most production is coming from the interval 2250-2285 m for each choke. The flow profile changed with the 32/64”, the interval 2250-2285 remained producing but the interval 2335-2375 m started receiving fluid from the upper interval. This cross flow increased after the well was shut in. The temperature log shows a normal behavior while the well is flowing through the 60/64” and 46/64” chokes, but changes as result of the cross flow with the 32/64” choke and with the well shut in. From the capacitance readings and pseudo fluid density (density from differential pressure) only oil is being produced, and there is a static water column at the sump.